Self-knowledge and knowledge management applications - Weed-Schertzer, Beverly (Emerald Publishing Limited, 2023)
Self-Knowledge plays an important role in making decisions and is instrumental in deciphering fact from false information: it is an inward tool, unique and changeable. Inward tools are essential in interpreting and processing information to create understanding and helping to determine illogical knowledge, whilst also fluctuating with the multifaceted and ever-changing awareness of the self that means the results of Self-Knowledge vary between individuals. Self-Knowledge and Knowledge Management Applications highlights and emphasizes the vital role of the human element in Knowledge Management, from which Self-Knowledge forms and functions. Self-Knowledge and Knowledge Management Applications covers the role and complexities of Self-Knowledge in the knowledge management process and Weed-Schertzer explains the separate and intertwined branches of Explicit Knowledge (tangible and transferrable), Tacit Knowledge (not easily transferrable) and Self-Knowledge (inward knowledge) and their applications in a business environment. Defining and explaining how Self-Knowledge enhances the application of each of these knowledge types when used both independently and collectively, Self-Knowledge and Knowledge Management Applications is essential reading for professionals and students across multiple disciplines, from business and management to strategy and technology.